INFLUENCE OF POTATO CULTIVARS AND N LEVELS ON CONTRIBUTION OF ORGANIC AMENDMENTS TO N NUTRITION - Kumar, Manoj; Trehan, S P (Potato Journal, 2013)
The field experiment was conducted to quantify the contribution of different organic amendments to N nutrition to potato cultivars of varying efficiency during winter season of 2006-07 and 2007-08 at Central Potato Research Station, Patna, India. All possible combinations of two varieties viz., Kufri Jyoti and Kufri Pukhraj, four nitrogen levels (0, 80, 160 and 240 kg/ha) and five organic amendments (control, rice straw @ 10 t/ha, farm yard manure @ 10 t/ha and 20 t/ ha and in situ green manuring with Sesbania aculeata) were replicated thrice in factorial randomized block design. Kufri Pukhraj was better yielder, agronomically more efficient, required less N to produce a given fixed yield in the presence of different organic amendments and derived higher per cent of its N nutrition from organic amendments. This cultivar also showed higher optimum yield level in the presence of all organic amendments and was more eco-friendly with respect to fertilizer N. Green manure added highest amount of N and showed highest efficiency. Kufri Pukhraj utilized more N from green manure and FYM and showed better efficiency than Kufri Jyoti. N equivalent of different organic amendments varied with tuber yield level and it was highest for green manure followed by FYM in both the cultivars. Optimum yield level, net return and benefit cost ratio were also higher for green manure followed by FYM.